Occupational resilience : an occupational therapy practice model facilitating high school participation post traumatic brain injury - Jacobs-Nzuzi Khuabi, Lee-Ann Juliana (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.